On the Splitting Principle of Beniamino Segre - Felisetti, Camilla; Fontanari, Claudio (2021)
We state and prove in modern terms a Splitting Principle first claimed by Beniamino Segre in 1938, which should be regarded as a strong form of the classical Principle of Connectedness.